Dorsal Aesthetic Line (DAL) Split Maneuver in Dorsal Preservation Rhinoplasty - Neves, José Carlos (Facial Plastic Surgery, 2024)
The dorsal aesthetic lines (DALs) osteotomies are a strategy to increase the plasticity of the dorsal pyramid to facilitate control of the convexity of the profile, width of the nasal dorsum, and define the eyebrow-tip aesthetic lines. It is also an alternative to lateral keystone area) disarticulation. This article discusses its advantages, indications, and the technical sequence of the DAL osteotomy procedure.
Keywords: DAL split maneuver; DAL osteotomies; LKA disarticulation; ballerina maneuver; preservation rhinoplasty